Grain position affects grain macronutrient and micronutrient concentrations in wheat - Calderini, Daniel F.; Ortiz-Monasterio, J. Ivan (International Food Policy Research Institute, 2003)
Which part of the spike of a wheat grain holds the highest concentration of nutrients? Researchers Daniel Calderini and Ivan Ortiz-Monasterio are among a pioneering group of scientists systematically examining this basic question of plant physiology and nutrition in wheat. The answers suggested by their research may help determine breeding strategies and continue progress in increasing bread grain production while also increasing life-sustaining micronutrients for people around the world. -- from Text